Caracterización hídrica y socioeconómica de la quebrada “Hualcanga”, ubicada en el páramo del Igualata, provincia del Tungurahua. - Briones Maza, José Alexander (2025)
This study focuses on the hydrological and socioeconomic characterization of the Hualcanga stream, located in the Nueva Vida community, Tungurahua province, Ecuador. The research emerged in response to environmental impacts caused by deforestation, agricultural expansion, livestock activities, and the resulting soil degradation, water contamination, and biodiversity loss. The lack of technical data on how these issues affect water resource availability underscores the need for an integrated approach that combines hydrology, environmental engineering, geography, and economics. The main objective is to characterize the stream using environmental and socioeconomic indicators to assess the effectiveness of conservation measures implemented in the upper part of the ecosystem. Field and laboratory methods were employed to analyze geomorphological, hydraulic, and water quality parameters, alongside surveys to evaluate the socioeconomic conditions within the area of influence. This study aims to contribute to the sustainable management of water resources in Tungurahua—a region critical for agriculture, drinking water supply, and hydroelectric power generation, yet vulnerable to climate change and anthropogenic pressures. The findings will support strategic decisions regarding conservation and sustainable development in the basin.